Unraveling the profile of posting companies - De Wispelaere, Frederic (Dve domovini, 2025)
Despite being central to intra-EU posting, the service provider (“the posting company”) remains understudied by scholars. Aiming to close this gap, this study examines posting companies (incl. the self-employed) in Slovenia. By linking them to the Orbis database, an analysis of Slovenian companies that received one or more Portable Documents A1 in 2022 shows that 8% of construction and 4% of manufacturing companies provided services abroad, compared to less than 2% of all Slovenian companies. For these companies, posting employees abroad has become a “business model”, with an average of 61% of employees posted abroad and 93.5% of turnover earned from exporting goods or providing services abroad.
Keywords: business model; labour market; migracije; migration; napotitve delavcev; podjetja za napotitve; poslovni model; posting companies; posting of workers; Slovenia; Slovenija; trg dela